2019
DOI: 10.3390/cancers11030392
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the mDia Formin-Assembled Cytoskeleton Is an Effective Anti-Invasion Strategy in Adult High-Grade Glioma Patient-Derived Neurospheres

Abstract: High-grade glioma (HGG, WHO Grade III–IV) accounts for the majority of adult primary malignant brain tumors. Failure of current therapies to target invasive glioma cells partly explains the minimal survival advantages: invasive tumors lack easily-defined surgical margins, and are inherently more chemo- and radioresistant. Much work centers upon Rho GTPase-mediated glioma invasion, yet downstream Rho effector roles are poorly understood and represent potential therapeutic targets. The roles for the mammalian Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
(81 reference statements)
2
21
0
Order By: Relevance
“…This was additionally accompanied by a shift in morphology with mDia2 knockdown. Migrating glioblastoma cells lost extensions and mesenchymal morphology, similar to findings reported with IMM2 treatment [19]. Compared to mDia1 and mDia2, we found that FHOD1 knockdown had similar effect on migration.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This was additionally accompanied by a shift in morphology with mDia2 knockdown. Migrating glioblastoma cells lost extensions and mesenchymal morphology, similar to findings reported with IMM2 treatment [19]. Compared to mDia1 and mDia2, we found that FHOD1 knockdown had similar effect on migration.…”
Section: Discussionsupporting
confidence: 88%
“…They found that the molecule IMM2 efficiently reduced the single cell migration from the neurosphere core. IMM2 treatment caused a morphologic shift toward ameboid morphology, also inhibiting the formation of microtubes [19]. Microtubes are recently found cellular extensions in glioblastoma, that keep glioblastoma cells connected as a network while migrating [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the top three pathways were cellular responses to stress, transcriptional regulation by RUNX1, and transcriptional regulation by MECP2 in the Reactome pathway analyses of target genes. We noted that the Rho GTPase pathway has been shown to be associated with infiltrative growth and invasion of glioblastoma [ 38 , 39 ]. In addition, RUNX1 is considered to a key factor participating in the malignant biological behavior of glioma cells [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The another is MTs stabilizers, which combines the polymerized heterodimer of α, β-tubulin with high a nity [7]. The polymerization of tubulin exhibit the key role in development and metastasis of HCC [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%